Learning Biology for Sustainable Development Using Hands-On Strategy: Can Gender Achievement Gap Reduce? - Onanuga, Peter Abayomi; Saka, Adewale Owodunni; Ogwokhademhe, Rita Pelumi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Despite the importance of for sustainable development, students’ performance in the subject has been inconsistent. Several interventions have been used to improve students’ learning of Biology but the inconsistency in performance persists. Thus, this study investigated the use of hands-on learning in enhancing students’ academic achievement. The research adopted a pretest-posttest control group quasi-experimental research design with 2x2 factorial. The study also examined the moderating effect of gender on academic achievement. Fifty-eight students offering Biology in the intact classes of two randomly selected schools participated in the study. The data was collected using a 25-item Biology Achievement Test for Students (BATS) subjected to face and content validities, and reliability test. The test-retest reliability method yielded a reliability coefficient of 0.68. The data analyses revealed a significant difference in the effect of strategy on the academic achievement of students in Biology (F (1,53) =8.595), p=0.05, but in favour of the conventional method of teaching. Further findings showed no significant difference in the effect of gender on the academic achievement of students (F (1,53) = 0.980), p>0.05. The researchers noted that hand-on activities are important for Biology learning and recommended that school authorities should allocate adequate time for that purpose.